(untitled) (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Environmental preservation by prioritizing waste management from the source is a very important program. In realizing effective processing, it is necessary to take action where organic household waste that is thrown away is utilized by processing it into eco-enzyme. The implementation of the community partnership program involves partners of the PKK women in Ranomuut Village, Paal 2 District, Manado City in the form of socialization and waste processing training. The organic kitchen waste that is processed is in the form of fruit peels (papaya, sunkis oranges, oranges, carrots, and apples). The fermentation process of kitchen waste is carried out for 3 months, then harvested and the resulting solution has a standard pH <4.0, namely 3.27, in addition to the results found are very good and there are no maggots. Eco-enzyme is stored in a shady place and is ready to use. Eco-enzyme has no expiration date and remains durable.